Association between SLCO1B1 T521C polymorphism and risk of statin-induced myopathy: a meta-analysis. Issue 6 (December 2018) - Xiang, Qian; Chen, Shu-qing; Ma, Ling-yue; Hu, Kun; Zhang, Zhuo; Mu, Guang-yan; Xie, Qiu-fen; Zhang, Xiao-dan; Cui, Yi-min
Abstract Numerous studies have illustrated the relationship between SLCO1B1 T521C polymorphism and statin-induced myopathy risk; however, this association is not consistent. Three electronic databases (PubMed, EMBASE, and the Cochrane Library) were searched from inception to October 2017 to identify potential studies. The summary odds ratios (ORs) with 95% confidence intervals (CIs) were calculated from different genetic models by using a random-effects model. Fourteen studies comprising 3265 myopathy patients and 7743 controls were included. The summary ORs suggested that 521CC (OR: 2.31; 95% CI: 1.15–4.63;P = 0.019), 521TC (OR: 1.34; 95% CI: 1.02–1.76;P = 0.034), and 521CC + TC (OR: 1.82; 95% CI: 1.32–2.51;P < 0.001) were associated with a greater risk of statin-induced myopathy than 521TT. The higher incidence of statin-induced myopathy was found to be significantly correlated with the C allele compared with the T allele (OR: 1.89; 95% CI: 1.36–2.62;P < 0.001). In addition, we observed that 521CC + TC was associated with an increased risk of myopathy in individuals who received simvastatin (OR: 2.35; 95% CI: 1.08–5.12;P = 0.032) or rosuvastatin (OR: 1.69; 95% CI: 1.07–2.67;P = 0.024) when compared with 521TT. The 521C allele was associated with a greater risk of cerivastatin-induced myopathy than the T allele (OR: 1.95; 95% CI: 1.47–2.57;P < 0.001). The findings of this study indicated that SLCO1B1 T521C was associated with a significantly higher risk of statin-induced myopathy, especially for simvastatin, rosuvastatin, and cerivastatin. Future studies should be conducted in subjects receiving specific types of drugs, and any potential adverse events need to be explored.